Evaluation of Clinical, Laboratory Findings, Treatment and Prognosis of Cases with Rhinoserebral Mucormycosis - Tartar, Ayse Sagmak; Kayali, Sumeyra; Akbulut, Ayhan (Bilimsel Tip Yayinevi, 2022)
Introduction: Mucormycosis is an opportunistic filamentous fungal infection that can progress rapidly. Different clinical pictures may occur depending on tissue and organ where the involvement is seen. Rhinoserebral mucormycosis, is the most common clinical form. We aimed to examine the patients diagnosed with rhinocerebral mucormycosis followed in our hospital with literature. Materials and Methods: Patients treating in our hospital between August 2009 and November 2020 with microbiologically and / or histopathologically confirmed rhinocerebral mucormycosis were evaluated retrospectively. Results: 2 (25%) of the patients were female and 6 (75%) of them were male. The average age was 56.37 +/- 9.318. All patients had at least one predisposing factor. Fever and headache symptoms were the most common. Surgical debridement and antifungal treatment were applied to all patients. 4 (50%) of the patients developed diffuse visual impairment and were discharged with sequelae. One (12.5%) of them was discharged with full recovery. 3 (37.5 %) of them died on the 12th day of hospitalization. Hemoglobin and Glaskow coma scores of patients with ex were significantly lower than the patients who were discharged, and SOFA scores were higher (p= 0.025, 0.031, 0.023, respectively). Conclusion: Nowadays, when the COVID-19 pandemic has not been controlled yet, most of the patients who receive immunosuppression due to COVID-19 also carry additional risk factors such as DM in terms of mucormycosis. Our article has contributed to raising awareness by drawing attention to risk factors, clinical signs and symptoms in mucormycosis. Training meetings should be organized for all medical doctors on this subject. In this way, mortality and sequelae rates can be improved with early diagnosis and treatment.
Keywords: Mucormycosis; Rhinoserebral mucormycosis; Paranasal sinus